1982
DOI: 10.2527/jas1982.5551027x
|View full text |Cite
|
Sign up to set email alerts
|

Learning Ability of Orphan Foals, of Normal Foals and of Their Mothers

Abstract: The maze learning ability of six pony foals that had been weaned at birth was compared to that of six foals reared normally. The foals' learning ability was also compared to their mothers' learning ability at the same task; the correct turn in a single choice point maze. The maze learning test was conducted when the foals were 6 to 8 mo old and after the mothered foals had been weaned. There was no significant difference between the ability of orphaned (weaned at birth) and mothered foals in their ability to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1983
1983
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…At its simplest level, relevant familiarisation begins in neonates with introductions to novel stimuli and is enhanced by foals' predisposition to play [8]. In horses, such experiences help shape social and performance skills [35,36]. For example, it has been demonstrated that foals under one year of age exhibit fewer fear responses and more interest in novel stimuli (notably when exposed to a regular feed-box and a feed-box covered with a black cloth) than horses aged between 2 and 15 years [37].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At its simplest level, relevant familiarisation begins in neonates with introductions to novel stimuli and is enhanced by foals' predisposition to play [8]. In horses, such experiences help shape social and performance skills [35,36]. For example, it has been demonstrated that foals under one year of age exhibit fewer fear responses and more interest in novel stimuli (notably when exposed to a regular feed-box and a feed-box covered with a black cloth) than horses aged between 2 and 15 years [37].…”
Section: Introductionmentioning
confidence: 99%
“…Hand-reared orphan foals are less emotional when placed in a novel environment than naturally reared foals. These same foals often show virtually no fear of humans and may be difficult to handle as adult horses [35,39]. Henry et al [40] reported that simply allowing foals to observe their dams being handled agreeably can have a calming effect on them in later life.…”
Section: Introductionmentioning
confidence: 99%